2018
DOI: 10.1007/s10071-018-1174-2
|View full text |Cite
|
Sign up to set email alerts
|

Proactive behavior, but not inhibitory control, predicts repeated innovation by spotted hyenas tested with a multi-access box

Abstract: Innovation is widely linked to cognitive ability, brain size, and adaptation to novel conditions. However, successful innovation appears to be influenced by both cognitive factors, such as inhibitory control, and non-cognitive behavioral traits. We used a multi-access box (MAB) paradigm to measure repeated innovation, the number of unique innovations learned across trials, by 10 captive spotted hyenas (Crocuta crocuta). Spotted hyenas are highly innovative in captivity and also display striking variation in be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
39
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 50 publications
7
39
2
Order By: Relevance
“…Finally, we evaluated whether individual consistency in persistence and in contact latency would emerge across the two tasks. Considering studies suggesting that these may indeed be personality traits ( Sih & Del Giudice, 2012 ; Johnson-Ulrich, Johnson-Ulrich & Holekamp, 2018 ), we predicted that our subjects would indeed be consistent in their persistence and contact latency across tasks.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Finally, we evaluated whether individual consistency in persistence and in contact latency would emerge across the two tasks. Considering studies suggesting that these may indeed be personality traits ( Sih & Del Giudice, 2012 ; Johnson-Ulrich, Johnson-Ulrich & Holekamp, 2018 ), we predicted that our subjects would indeed be consistent in their persistence and contact latency across tasks.…”
Section: Introductionmentioning
confidence: 98%
“…Studies have found that animals that spend longer engaged in a task also tend to utilize a greater variety of behaviours ( Griffin, Diquelou & Perea, 2014 ; Logan, 2016 ; Johnson-Ulrich, Johnson-Ulrich & Holekamp, 2018 ). In line with this, we expected to find a positive correlation between persistence and motor diversity.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found animals that spend longer engaged in a task to also tend to utilize a greater variety of behaviours (Griffin, Diquelou & Perea, 2014;Logan, 2016;Johnson-Ulrich, Johnson-Ulrich & Holekamp, 2018). In line with this, we expected to find a positive correlation between persistence and motor diversity.…”
Section: Introductionsupporting
confidence: 71%
“…Accordingly, several studies have shown that individual differences in behavioral plasticity or purported measures of plasticity such as reversal learning rate (e.g., Guillette et al, 2010 ; Lucon-Xiccato & Bisazza, 2014 ; Pintor et al, 2014 ) are associated with differences in personality traits ( Gibelli & Dubois, 2017 ; Guayasamin, Couzin & Miller, 2017 ; Guido et al, 2017 ; Mazza et al, 2018 ; see also reviews by Mathot et al, 2012 and Stamps, 2016 ), hence suggesting that certain behavioral traits or particular skills that are associated with them could prevent individuals from exhiting optimal behavioral plasticity. By contrast, however, several authors reported the opposite effect or no effect of personality type on how individuals respond to changing stimuli (e.g., Logan, 2016b ; Bensky et al, 2017 ), whereas the few studies that have measured behavioral plasticity for the same individuals in several traits or contexts ( Biro, Beckmann & Stamps, 2010 ; Morand-Ferron, Varennes & Giraldeau, 2011 ; Logan, 2016a ) or from different proxies ( Brucks et al, 2017 ; Johnson-Ulrich, Johnson-Ulrich & Holekamp, 2018 ) found weak or no support for a general plasticity. For instance, despite most individuals becoming more active and bold as temperature increased in damselfish ( Pomacentrus bankanensis ), Biro, Beckmann & Stamps (2010) found that the degree of plasticity in activity of a given individual was unrelated to its level of plasticity in boldness.…”
Section: Introductionmentioning
confidence: 92%